2020
DOI: 10.3390/en13051270
|View full text |Cite
|
Sign up to set email alerts
|

Novel Experimental Device to Monitor the Ground Thermal Exchange in a Borehole Heat Exchanger

Abstract: Ground source heat pump (GSHP) systems are becoming popular in space heating and cooling applications. Despite this fact, in most countries, the role of this energy is not as important as it should be nowadays according to its capabilities for energy generation without CO2 emissions, mainly due to the lack of technical knowledge about GSHP performance. The analysis of the physical processes that take part in the geothermal exchanges is necessary to allow the optimal exploitation of the geothermal resources. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…DS18B20 sensors are used in engineering projects (e.g. for temperature monitoring in hydrotechnical devices [25], studies of concrete properties [26], industrial pipelines [27], geothermal installations [28,29], environmental temperature (e.g. measurements of substrate temperature [5,12,[14][15][16][30][31][32]) and in karst hydrogeology [17].…”
Section: Soil Temperature Sensormentioning
confidence: 99%
“…DS18B20 sensors are used in engineering projects (e.g. for temperature monitoring in hydrotechnical devices [25], studies of concrete properties [26], industrial pipelines [27], geothermal installations [28,29], environmental temperature (e.g. measurements of substrate temperature [5,12,[14][15][16][30][31][32]) and in karst hydrogeology [17].…”
Section: Soil Temperature Sensormentioning
confidence: 99%
“…Sáez Blázquez et al proposed an experimental novel device that provides an inexpensive, less time-consuming and reliable approach to measuring thermal conductivity. This approach can replace or supplement well-known but expensive methods such as the thermal response test (TRT) [67]. A very extensive review on TRTs of ground-coupled heat pump systems can be found in the work of Zhang et al covering both in situ research and mathematical models [68].…”
Section: Introductionmentioning
confidence: 99%
“…By comparing these experimental data with the model describing the heat exchange between the liquid and the ground, it is possible to estimate the thermal properties of the ground [57,[59][60][61][62]. Sáez Blázquez et al [63] proposed a new experimental device that provides an inexpensive, less time-consuming, and reliable approach to measuring thermal conductivity. This approach may replace or supplement well-known but expensive methods such as the thermal response test (TRT).…”
Section: Introductionmentioning
confidence: 99%